Pathways to an integrated understanding of marine environments and ecosystems in the Asia-Pacific Region - Adiwira, Hanani; Yasunaka, Sayaka; Kass, Jamie M.; Açıkbaş, Ayşe H. O.; Adiningsih, Sekar; Gairin, Emma; Ilham, Hovaldo B. C.; Lahcene, Elisa; Li, Yanguo; Nishihira, Gaku; Peñalver-Pereira, Paula; Sie, Florence M. P.; et al. (Frontiers in Marine Science, 2025)
The Asia-Pacific Region (APR) encompasses a vast geographical area rich in marine biodiversity that plays critical roles in global ecological stability and climate regulation, but it also faces daunting challenges in maintaining these roles under global change. Environmental dynamics in the APR manifest regularly over a range of timescales, including storms, earthquakes, floods, and extreme heat events. Further, coastal and marine ecosystems, including extensive commercial fisheries and coral reefs, are under threat from intense resource extraction and increasingly frequent marine heatwaves. Knowledge gaps for understanding these complex systems are aggravated by substantial barriers to cross-national efforts caused by the region’s vast diversity of cultures, languages, socioeconomics, politics, and management practices. Effective management of marine resources in the APR will necessitate multidisciplinary research based on continuous, region-wide observations supported by robust collaborations. In 2023, we gathered APR researchers across disciplines to discuss these issues and find solutions during a thematic seminar and workshop program at Tohoku University in Japan. Based on the results of this program, we present a review of the current state of APR marine ecosystems, raise key questions addressable through multidisciplinary approaches, and identify future priorities for the region. We conclude that sustaining biodiversity, ecosystem functions, and climate resilience in the APR will depend on stronger interdisciplinary collaboration, better integration of biological and geophysical data, and broader access to marine observations. These efforts are both urgent and essential for supporting better science-based policy decisions to address the escalating effects of global change on marine systems across the region.